Hubungan Faktor Iklim dan Ketersediaan Air Bersih dengan Kejadian Diare di Kota Kupang Tahun 2011-2015 (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: This study aims to determine the relation of climate factors and the availability of clean water with the diarrhea occurrence in Kupang City from the years of 2011-2015. Method: This study used ecological study design by using pearson correlation test with spearman correlation test alternative and uses secondary data consisting of diarrhea case data, water discharge data and climate data of Kupang City from 2011-2015. Results: The results of statistical analysis known that variables that have relationship with diarrhea occurrence in Kupang City are rainfall (p = 0.0001; r = -0.48), humidity lag1-3 (p = 0,000; r = -0, 5), wind speed lag2-3 (p = 0,000; r = 0,5 and clean water supply (p = 0.0002; r = - 0.47) while the air temperature variable has no relation with diarrhea occurrence in Kupang city in 2011 -2015 (p value> 0,05). Conclusion: Based on the research results, it was concluded that variables of rainfall, humidity lag1-3, wind speed lag2-3 and availability of clean water indicate a relationship with the incidence of diarrhea in Kupang City from the years of 2011-2015.